(untitled) (Palíndromo, 2020)
This visual essay is composed by the work called “The Man Who Was Just a Half”, in which processes of creation in the Contemporary Arts are articulated, exploring the possibilities of the body and object in the urban space and the exchanges that can be established between the potentialities of space and human subjectivity.